Small bowel disorders - Ratnaike, Rnjit N. (London Arnold, 2000)
This work provides comprehensive information on small bowel disorders. Its 18 chapters address anatomy, defence mechanisms, the physiology of absorption and secretion, normal and abnormal pathology, tests of function, disease states and management. There is also a chapter on surgery.
Keywords: Intestins -- Malalties